VULNERABILITY OF AGRICULTURE TO CLIMATE CHANGE IN SERBIA – FARMERS’ ASSESSMENT OF IMPACTS AND DAMAGES - Stričević, Ružica J.; Lipovac, Aleksa D.; Prodanović, Slaven A.; Ristovski, Marijana A.; Petrović Obradović, Olivera T.; Djurović, Nevenka Lj.; Djurović, Dejan B. (Journal of Agricultural Sciences (Belgrade), 2020)
Considering the already observed trends of increasing air temperatures, changes in precipitation regimes, and extension of the growing season, as well as predictions that climate conditions in Serbia will deteriorate and the risk to farming increase, the objective of this research is to assess the vulnerability of agriculture in Serbia to climate change, based on farmers’ perceptions. A team of experts in all areas of agriculture and soil and water management compiled a questionnaire for a semi-open online survey. The snowball sampling approach was followed, relying on personal contacts and social media. In total, 141 farmers responded to the questionnaire. The data is evaluated through descriptive statistics. The differences by region, activity and topography are tested by ANOVA and Student’s t test. The feedback is used to assess the damages sustained by farmers due to climate change and reduced revenues in their respective areas of agricultural activity. Certain positive effects of climate change are also identified. A need for training in climate change impact mitigation is noted. The collected data are analyzed by descriptive statistics. The surveyed farmers believe that the most important effects of climate change are periods of extreme high temperature, droughts, late spring frost, and hail. Climate change seems to be reducing yields, facilitating the appearance of new diseases and pests, and causing a lower tolerance to existing diseases and pests. Farmers express considerable interest in climate change impact adaptation and mitigation training.